Offense Type as Determinant of Revenge and Forgiveness After Victimization: Adolescents' Responses to Injustice and Aggression. (2nd January 2018) - Gerlsma, Coby; Lugtmeyer, Valerie
ABSTRACT: Victims of injustice and aggression may have strong feelings about the perpetrator(s) that may impede their efforts to cope with the victimizing experience. We examined to what extent adolescents' interpersonal responses to victimization in terms of revenge and forgiveness depend on offense type. Of 455 Dutch students from various educational levels, 379 participants reported being victimized by incidents of injustice, aggression, or violence. These incidents were categorized according to type and related to respondents' self-reported revenge, avoidance, and benevolence toward the perpetrator. Victims of criminal offenses (physical and sexual violence, theft, and threat) reported less forgiving motivations than victims of noncriminal transgressions (bullying, ostracism, and other forms of indirect aggression). Sexual violence primarily elicited avoidance, rather than revenge. Gender differences in responses to victimization depended on offense type, too. Hence, to enhance our knowledge about revenge and forgiveness after victimization, future studies may need to take offense characteristics into account.